Battery

By controlling the particle size DV50 of the silicon carbon composite material in the battery, the depth ratio of the particle size DV50 and the pressure groove grooves, the problem of early tearing of the lax groove caused by the expansion of the silicon material, and the normal operation of the battery and the safe leakage.

CN119340490APending Publication Date: 2025-01-21ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411771119.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The specific capacity of traditional graphite materials is close to their theoretical specific capacity, which is difficult to increase and cannot meet the market demand of high-energy-density batteries. At the same time, the volume expansion of silicon materials during the deintercalation of lithium is easily caused to tear the battery pressure relief grooves in advance, affecting the impact of Normal use of the battery.

Method used

By controlling the particle size Dv50 of the silicon carbon composite material in the negative electrode sheet and the depth of the pressure relief groove, a relationship is established to ensure that the ratio between the Dv50 of the silicon carbon composite material and the depth of the pressure relief groove is between 0.06 and 0.6, thereby preventing the expansion of the negative electrode sheet. Causes premature tearing of the pressure relief groove.

Benefits of technology

It is achieved to prevent the pressure of the groove in advance during the charging and discharge process, ensure the normal operation of the battery, and ensure that the battery can timely disclose pressure in time when the battery is out of control to avoid the battery fire and explosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340490A_ABST
    Figure CN119340490A_ABST
Patent Text Reader

Abstract

The battery comprises a shell and a battery cell, a pressure relief groove is formed in the shell, and the battery cell is arranged in the shell; the battery cell comprises a positive plate, a negative plate and a diaphragm positioned between the positive plate and the negative plate; the negative plate comprises a negative current collector and a negative active material layer located on the negative current collector, and the negative active material layer comprises a silicon-carbon composite material; and the ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.06-0.6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy, and in particular relates to a battery. Background Art

[0002] With the continuous increase in market demand, the development of lithium-ion batteries with high energy density and high fast charging efficiency has become a future development trend; the specific capacity of traditional graphite materials is close to its theoretical specific capacity (372mAh / g) and it is difficult to improve it further, which cannot meet the market demand for high energy density batteries.

[0003] The pressure relief groove is set to allow gas to be discharged as quickly as possible to avoid battery explosion when the battery cell is in thermal runaway. The theoretical specific capacity of silicon material (4200mAh / g) is more than 10 times that of graphite material, and it is considered to be the most promising next-generation high-energy density lithium-ion battery material. However, during the process of silicon material deintercalation and extraction of lithium, the volume of silicon material expands by 120% to 300%, and the negative electrode sheet expands, which can easily cause the battery pressure relief groove to tear prematurely, affecting the normal use of the battery. Summary of the invention

[0004] Therefore, the present invention provides a battery, which establishes a connection between the particle size Dv50 of the silicon-carbon composite material in the negative electrode sheet and the depth of the pressure relief groove, thereby preventing the negative electrode sheet from expanding during charging and discharging and causing the pressure relief groove to tear prematurely, thereby ensuring the normal operation of the battery.

[0005] To this end, the present invention provides the following technical solutions.

[0006] The present invention provides a battery, comprising a shell and a battery cell, wherein the shell is provided with a pressure relief groove, and the battery cell is arranged in the shell;

[0007] The battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector, and the negative electrode active material layer comprises a silicon-carbon composite material;

[0008] The ratio of the particle size Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.06 to 0.6.

[0009] In a possible implementation, the particle size Dv50 of the silicon-carbon composite material is 5 to 20 μm, preferably 6 to 12 μm;

[0010] In a possible implementation, the depth of the pressure relief groove is 35-85 μm, preferably 40-80 μm. If the pressure relief groove is too deep, it will be broken during the drop test, causing the battery to catch fire and explode. If the pressure relief groove is too shallow, it cannot be broken in time during the furnace temperature test, and the heat and gas cannot be dissipated, which may cause the battery to catch fire and explode.

[0011] In a possible implementation, the shell includes a body and a cover plate, the body has a receiving cavity for receiving the battery cell, the receiving cavity has an opening, and the cover plate is buckled on the opening; a bonding member is provided on a side surface of the battery cell facing the cover plate;

[0012] A: B = 0.015 ~ 2;

[0013] A is the mass percentage of silicon in the negative electrode active material layer;

[0014] B is the percentage of the projected area of ​​the adhesive in the thickness direction of the battery cell to the projected area of ​​the electrode bonded by the adhesive in the thickness direction of the battery cell;

[0015] Optionally, A is 1.5% to 40%;

[0016] Optionally, B is 20% to 95%.

[0017] In a possible implementation manner, the pressure relief groove is provided on the cover plate;

[0018] In a possible implementation manner, the pressure relief groove and the bonding member are staggered in projection in the thickness direction of the shell;

[0019] In a possible implementation manner, the pressure relief groove and the projection of the negative electrode sheet in the thickness direction of the shell are staggered.

[0020] In a possible implementation manner, the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.35 to 0.9, preferably 0.45 to 0.8.

[0021] Optionally, the depth of the pressure relief groove is 35 to 85 μm, preferably 40 to 80 μm;

[0022] Optionally, the cover plate has a thickness of 70 to 200 μm, preferably 70 to 160 μm;

[0023] In a possible implementation, the average sphericity of the silicon-carbon composite material is 0.5-1.

[0024] In a possible implementation manner, the porosity of the negative electrode sheet is 5% to 50%.

[0025] In a possible implementation manner, the OI value of the negative electrode sheet is 3-35.

[0026] In a possible implementation, the silicon-carbon composite material includes a porous carbon substrate, silicon dispersed in the porous carbon pores, and a carbon coating layer located on the surface of the porous carbon substrate;

[0027] Optionally, the carbon coating layer is amorphous carbon;

[0028] Optionally, the mass content of silicon in the silicon-carbon composite material is 30% to 90%, preferably 35% to 70%.

[0029] In a possible implementation, the silicon-carbon composite material includes open pores and / or closed pores, where closed pores refer to pores in the porous carbon substrate that are covered by the carbon coating layer, and open pores refer to pores on the porous carbon substrate that are not covered by the carbon coating layer;

[0030] Optionally, the area of ​​the open pores is smaller than the area of ​​the closed pores.

[0031] The technical solution of the present invention has the following advantages:

[0032] 1. The battery of the present invention comprises a shell and a battery cell, wherein the shell is provided with a pressure relief groove, and the battery cell is arranged in the shell; the battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked; the negative electrode sheet comprises a negative electrode collector and a negative electrode active material layer located on the negative electrode collector, and the negative electrode active material layer comprises a silicon-carbon composite material; the ratio of the particle size Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.06 to 0.6.

[0033] Dv50 refers to the median particle size of the silicon-carbon composite material. The silicon-carbon composite material will expand rapidly during the charge and discharge process, so that the battery cell is easily squeezed against the shell and the cover plate, causing the pressure relief groove (thinned part) to be torn in advance. When the silicon-doped negative electrode is fully charged and in the late cycle, the expansion of the silicon-carbon composite material causes different stresses in different positions of the battery cell, and the uneven stress causes the battery cell to deform. Even after the expansion, the active particles lose electrical contact, resulting in lithium precipitation and even short circuit fire. Therefore, the present invention limits the ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove, so that the battery can achieve directional and timely explosion (that is, the pressure relief groove normally realizes its pressure relief function) while preventing the steel shell battery from rupturing the pressure relief groove in advance due to excessive expansion of the negative electrode sheet during the charge and discharge process.

[0034] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 Schematic diagram of battery structure;

[0037] Figure 2 A is the SEM image of silicon-carbon composite material;

[0038] Figure 3 This is the SEM image B of the silicon-carbon composite material.

[0039] Reference numerals:

[0040] 1-cover plate; 101-pressure relief groove; 2-adhesive member; 3-battery cell; 4-body. DETAILED DESCRIPTION

[0041] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0042] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0043] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0044] In a first aspect, the present invention provides a battery, comprising a shell and a battery cell, wherein the shell is provided with a pressure relief groove, and the battery cell is arranged in the shell;

[0045] The battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector, and the negative electrode active material layer comprises a silicon-carbon composite material;

[0046] The ratio of the particle size Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.06 to 0.6.

[0047] The battery cell is a rolled core, a stacked core or a composite battery cell (rolled core + stacked core).

[0048] By limiting the Dv50 of the silicon-carbon composite material and the depth of the pressure relief groove within the scope of the present invention, the battery can be directional and exploded in time, while preventing the steel shell battery from excessive expansion of the negative electrode sheet during the charge and discharge process, thereby causing the pressure relief groove to rupture prematurely.

[0049] As an example, the ratio of Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove may be 0.06, 0.10, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.3, 0.4, 0.5 or 0.6.

[0050] In an optional embodiment, the particle size Dv50 of the silicon-carbon composite material is 5 to 20 μm, preferably 6 to 12 μm; illustratively, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 18 μm, 19 μm or 20 μm. A silicon-carbon composite material with a smaller Dv50 can help reduce the mechanical stress and stress concentration of the silicon-carbon composite material during the charging and discharging process, help maintain the structural stability of the silicon-carbon composite material, reduce the rupture or structural damage of the particles, and thus extend the service life of the battery. However, if the particle size of the silicon-carbon composite material is too small, the side reactions of the silicon-carbon composite material with the electrolyte will increase, aggravating the pulverization of the particles and thickening the negative electrode sheet. The Dv50 of the silicon-carbon composite material affects the expansion rate of the particles and the rebound size of the electrode sheet thickness after full charge and cycle.

[0051] In an optional embodiment, the depth of the pressure relief groove is 35 to 85 μm, preferably 40-80 μm. Exemplarily, it can be 35 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm or 85 μm. The depth of the pressure relief groove affects the safety performance of the battery. If it is not within the scope of this application, during normal charging and discharging, the expansion of the silicon-carbon composite material can easily lead to the overall deformation of the negative electrode sheet or even the battery cell, thereby causing the pressure relief groove to rupture prematurely.

[0052] In an optional embodiment, the shell includes a body and a cover plate, the body has a receiving cavity for receiving the battery cell, the receiving cavity has an opening, and the cover plate is buckled on the opening; a bonding member is provided on a side surface of the battery cell facing the cover plate;

[0053] A: B = 0.015 ~ 2;

[0054] A is the mass percentage of silicon element in the negative electrode active material layer;

[0055] B is the percentage of the projected area of ​​the adhesive in the thickness direction of the battery cell to the projected area of ​​the electrode bonded by the adhesive in the thickness direction of the battery cell.

[0056] The adhesive member can be hot melt adhesive or adhesive tape.

[0057] A: B is limited within the scope of the present invention, and can effectively disperse the mechanical stress of the silicon-carbon composite material in the negative electrode sheet during the charging and discharging process while improving the energy density. The force between the battery cell and the shell is transmitted through the adhesive, and the force applied by the battery cell to the adhesive is effectively dispersed, so that the force per unit area actually applied to the shell will be reduced, thereby preventing the negative electrode sheet of the steel shell battery from expanding too much during the charging and discharging process, thereby causing the pressure relief groove to rupture prematurely, and improving the protection effect of the shell on the battery cell. Similarly, the reaction force per unit area applied to the battery cell will also be reduced, thereby preventing the battery cell from folding at the corners or edges.

[0058] Illustratively, A:B can be 0.015, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8 or 2.0.

[0059] In an optional embodiment, A is 1.5% to 40%. Within this range, the amount of lithium ions intercalated and deintercalated in the silicon-carbon composite material can be fully utilized, and while the energy density is increased, the excessive content of the silicon-carbon composite material is prevented from causing excessive expansion of the pole piece.

[0060] Optionally, A is 7% to 20%; B is 20% to 95%, preferably 50% to 90%.

[0061] In an optional embodiment, the projections of the pressure relief groove and the bonding member in the thickness direction of the shell are staggered;

[0062] In a possible implementation manner, the pressure relief groove and the projection of the negative electrode sheet in the thickness direction of the shell are staggered.

[0063] In an optional embodiment, the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.35 to 0.9, preferably 0.45 to 0.8. Exemplarily, the ratio of the depth of the pressure relief groove to the thickness of the cover plate can be 0.35, 0.45, 0.5, 0.6, 0.7, 0.8 or 0.9.

[0064] Optionally, the depth of the pressure relief groove is 35 to 85 μm, preferably 40 to 80 μm.

[0065] Optionally, the cover plate has a thickness of 70 to 200 μm, preferably 70 to 160 μm, and illustratively may be 70 μm, 80 μm, 90 μm, 100 μm, 105 μm, 110 μm, 130 μm, 150 μm, 180 μm or 200 μm.

[0066] The ratio of the depth of the pressure relief groove and the thickness of the cover plate is within the scope of the present application, which can ensure that the pressure relief groove cracks in time during thermal runaway while ensuring the structural strength of the shell when the battery cell is working normally.

[0067] In an optional embodiment, the peak intensity ratio gs of the characteristic peak 1 of 0.25V to 0.3V and the characteristic peak 2 of 0.4V to 0.45V of the first-week lithium de-lithiation DQ / DV curve of the battery is in the range of 1.0≤gs≤3.0. Within this range, the secondary battery is more conducive to improving the cycle performance and reducing the expansion performance of the secondary battery while maintaining a high specific capacity, thereby preventing the negative electrode sheet of the steel shell battery from expanding too much during the charge and discharge process, thereby causing the pressure relief groove to rupture prematurely, and improving the protective effect of the shell on the battery cell.

[0068] In an optional embodiment, the average sphericity of the silicon-carbon composite material is 0.5 to 1. Compared with non-spherical particles, the higher the sphericity, the closer the shape is to a sphere, so that when its volume expands, the impact on the pole piece structure is smaller, and the overall structural stability of the pole piece can be maintained during expansion; in addition, spherical particles can improve the mechanical strength and stability of the material, reduce the stress concentration between particles caused by expansion, and thus reduce the risk of mechanical wear and damage of the material during the cycle. Exemplarily, the average sphericity of the silicon-carbon composite material can be 0.5, 0.6, 0.7, 08, 0.9 or 1.

[0069] In an optional embodiment, the porosity of the negative electrode sheet is 5% to 50%. The porosity within this range can provide more space to accommodate the expansion of the silicon-carbon composite material, better absorb the volume change of the silicon-carbon composite material caused by charging and discharging, and help maintain the structural stability and cycle life of the motor.

[0070] In an optional embodiment, the OI value of the negative electrode sheet is 3 to 35. The OI value within this range can enhance the network structure of silicon, reduce the structural collapse caused by the volume expansion of the silicon-carbon composite material during the charging and discharging process, and make the silicon-carbon composite material more effectively embed and deintercalate lithium ions during the charging and discharging process, thereby helping to improve the energy density, cycle life and safety of the battery. Exemplarily, the OI value of the negative electrode sheet can be 3, 5, 8, 10, 15, 20, 25, 30 or 35.

[0071] In an optional embodiment, the silicon-carbon composite material comprises a porous carbon substrate, silicon dispersed in the porous carbon pores, and a carbon coating layer located on the surface of the porous carbon substrate;

[0072] Optionally, the carbon coating layer is amorphous carbon;

[0073] Optionally, the mass content of silicon in the silicon-carbon composite material is 30% to 90%, preferably 35% to 70%. Exemplarily, it can be 30%, 40%, 42%, 45%, 48%, 50%, 60%, 70%, 80% or 90%.

[0074] In an optional embodiment, the silicon-carbon composite material includes open pores and / or closed pores, where closed pores refer to pores in the porous carbon substrate that are covered by the carbon coating layer, and open pores refer to pores on the porous carbon substrate that are not covered by the carbon coating layer. Figure 2 , Figure 3 shown.

[0075] Optionally, the area of ​​the open pores is smaller than the area of ​​the closed pores, which can effectively inhibit the expansion of the silicon-carbon composite material, prevent the outer carbon coating layer from pulverizing and rupturing, and reduce side reactions.

[0076] Example 1

[0077] This embodiment provides a battery such as Figure 1 As shown, it includes a shell and a battery cell 3, the shell is provided with a pressure relief groove 101, and the battery cell 3 is arranged in the shell.

[0078] The shell includes a body 4 and a cover plate 1 . The body 4 has a receiving cavity for receiving the battery cell. The receiving cavity has an opening. The cover plate 1 is buckled on the opening.

[0079] like Figure 1 The L-shape shown on the cover plate 1 is the pressure relief groove 101, which is formed by etching on the cover plate 1 through a laser etching process. The wall thickness of the location where the pressure relief groove 101 is provided on the cover plate 1 is thinned. When the battery cell in the shell is in thermal runaway, the gas will press against the thinned location, and the thinned location will burst first, thereby discharging the gas. The depth of the pressure relief groove 101 refers to the depth of the thinned portion of the cover plate 1. It should be noted that the pressure relief groove 101 can be thinned from the outside of the cover plate 1 to the inside, or from the inside of the cover plate 1 to the outside.

[0080] The battery cell 3 includes a positive electrode sheet, a separator and a negative electrode sheet which are stacked. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode active material layer includes a silicon-carbon composite material.

[0081] A bonding member 2 is provided on the surface of the battery core 3 facing the cover plate. In this embodiment, the bonding member is a hot melt adhesive.

[0082] A positive pole is arranged on a side plate of the shell body 4, and the positive pole includes a pole part connected to the positive pole ear of the battery cell. An inner insulating sheet and an outer insulating sheet are arranged between the pole and the shell, and the pole is passed through the shell from the outside to the inside and connected to the ear.

[0083] A through hole for liquid injection is also provided on a side plate of the shell body 4. After the liquid injection is completed, the liquid injection hole is sealed with a sealing nail. The sealing nail includes a three-layer structure, including a metal ring, PP glue and a metal sheet welded to the shell. The metal ring is formed with a hole connected to the liquid injection hole. The PP glue is U-shaped with a U-shaped hole. The metal sheet covers the sealed liquid injection hole. The function of the sealing nail is to release pressure from the liquid injection hole when the internal short circuit of the steel shell fails and the PP glue of the sealant melts due to heat.

[0084] The projections of the pressure relief groove and the bonding piece in the thickness direction of the shell are staggered (ie, the projections do not overlap), and the projections of the pressure relief groove and the negative electrode sheet in the thickness direction of the shell are staggered.

[0085] The preparation method of the battery of this embodiment includes:

[0086] (1) Preparation of negative electrode

[0087] Silicon-carbon composite material, graphite, conductive carbon black, polyacrylic acid, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 43.1:53.8:0.5:1.3:0.4:0.9, added into deionized water and stirred evenly to form a negative electrode slurry, which is then evenly coated on the positive electrode current collector copper foil, and then dried and rolled to form a negative electrode sheet.

[0088] In the negative electrode active material layer of the negative electrode sheet, the mass percentage A of silicon element in the negative electrode active material layer is 19.38%. The porosity of the negative electrode sheet is 27.8%. The OI value of the negative electrode sheet is 32.67.

[0089] The silicon-carbon composite material includes a porous carbon substrate, silicon dispersed in the porous carbon pores, and a carbon coating layer located on the surface of the porous carbon substrate; the carbon coating layer is amorphous carbon, and the mass content of silicon in the silicon-carbon composite material is 45%. The silicon-carbon composite material includes open pores and closed pores, and the area of ​​the open pores is smaller than the area of ​​the closed pores.

[0090] The Dv50 of the silicon-carbon composite material in this embodiment is 7.8 μm. The average sphericity of the silicon-carbon composite material is 0.65.

[0091] (2) Preparation of positive electrode

[0092] Positive electrode sheet: Lithium cobalt oxide (LCO), polyvinylidene fluoride (PVDF), and conductive carbon (Super P) are dissolved in N-methylpyrrolidone (NMP) in a mass ratio of 98:1:1, stirred evenly to form a positive electrode slurry, and then evenly coated on the positive electrode current collector aluminum foil. After drying and rolling, the positive electrode sheet is made.

[0093] (3) Battery assembly

[0094] The negative electrode sheet, the separator and the positive electrode sheet are stacked in order to obtain a battery cell, and then the battery cell is packaged with a shell and a cover plate, and then liquid injection, secondary sealing, formation, sorting and other processes are carried out to obtain the battery.

[0095] The lithium salt used in the electrolyte of this embodiment is lithium hexafluorophosphate (LiPF6) with a concentration of 1M, the organic solvent is a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) prepared in a mass ratio of 3:4:3, and the additives are 3wt% fluoroethylene carbonate (FEC) and 1wt% vinylene carbonate.

[0096] In this embodiment, the depth of the pressure relief groove is 50 μm, the thickness of the cover plate is 100 μm, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.5. The ratio of Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.156.

[0097] In this embodiment, A=19.38%, and the percentage of the projection area of ​​the adhesive member 2 in the thickness direction of the battery cell to the projection area of ​​the electrode bonded by the adhesive member 2 in the thickness direction of the battery cell B=90%. A:B=0.22.

[0098] Example 2

[0099] The present embodiment provides a battery, which is basically the same as the embodiment 1, except that, in the present embodiment, the depth of the pressure relief groove is 78 μm, the thickness of the cover plate is 150 μm, the Dv50 of the silicon-carbon composite material is 5 μm, the ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.06, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.52.

[0100] Example 3

[0101] The present embodiment provides a battery, which is basically the same as the embodiment 1, except that, in the present embodiment, the depth of the pressure relief groove is 40 μm, the thickness of the cover plate is 75 μm, the Dv50 of the silicon-carbon composite material is 20 μm, the ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.5, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.53.

[0102] Example 4

[0103] This embodiment provides a battery, which is basically the same as Embodiment 1, except that, in this embodiment, the depth of the pressure relief groove is 78 μm, the ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.10, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.78.

[0104] Example 5

[0105] This embodiment provides a battery, which is basically the same as Embodiment 1, except that, in this embodiment, the depth of the pressure relief groove is 70 μm, the ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.111, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.7.

[0106] Example 6

[0107] This embodiment provides a battery, which is basically the same as the embodiment 1, except that the Dv50 of the silicon-carbon composite material is 6.3 μm. The ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.13.

[0108] Example 7

[0109] This embodiment provides a battery, which is basically the same as the embodiment 1, except that the Dv50 of the silicon-carbon composite material is 11.7 μm. The ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.234.

[0110] Example 8

[0111] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the depth of the pressure relief groove is 45 μm, and the Dv50 of the silicon-carbon composite material is 5.1 μm. The ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.113, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.45.

[0112] Example 9

[0113] This embodiment provides a battery, which is basically the same as the embodiment 1, except that B=20% and A:B=0.97.

[0114] Example 10

[0115] This embodiment provides a battery, which is basically the same as the embodiment 1, except that B=80% and A:B=0.24.

[0116] Embodiment 11

[0117] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the silicon-carbon composite material, graphite, conductive carbon black, polyacrylic acid, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 66.7:30.2:0.5:1.3:0.4:0.9, and A=30%, A:B=0.33 are measured.

[0118] Example 12

[0119] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the silicon-carbon composite material, graphite, conductive carbon black, polyacrylic acid, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 3.3:93.6:0.5:1.3:0.4:0.9, and A=1.5%, A:B=0.017 are measured.

[0120] Example 13

[0121] This embodiment provides a battery, which is basically the same as the embodiment 1, except that the silicon-carbon composite material, graphite, conductive carbon black, polyacrylic acid, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 88.9:8.0:0.5:1.3:0.4:0.9, and A=40%. In this embodiment, B=25%, and A:B=1.6.

[0122] Embodiment 14

[0123] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the thickness of the cover plate is 90 μm, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.56.

[0124] Embodiment 15

[0125] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the thickness of the cover plate is 110 μm, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.45.

[0126] Example 16

[0127] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the thickness of the cover plate is 95 μm, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.53.

[0128] Embodiment 17

[0129] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the thickness of the cover plate is 105 μm, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.48.

[0130] Embodiment 18

[0131] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the average sphericity of the silicon-carbon composite material is 0.5.

[0132] Embodiment 19

[0133] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the average sphericity of the silicon-carbon composite material is 0.91.

[0134] Embodiment 20

[0135] This embodiment provides a battery, which is basically the same as the embodiment 1, except that the porosity of the negative electrode sheet is 5%.

[0136] Embodiment 21

[0137] This embodiment provides a battery, which is basically the same as the embodiment 1, except that the porosity of the negative electrode sheet is 50%.

[0138] Embodiment 22

[0139] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the OI value of the negative electrode sheet is 3.

[0140] Embodiment 23

[0141] This embodiment provides a battery, which is basically the same as that of Embodiment 1, except that the OI value of the negative electrode sheet is 35.

[0142] Embodiment 24

[0143] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the mass ratio of the silicon-carbon composite material, graphite, conductive carbon black, polyacrylic acid, sodium carboxymethyl cellulose and styrene-butadiene rubber is 48.5:48.5:0.5:1.3:0.4:0.9, and the mass content of silicon in the silicon-carbon composite material is 40%.

[0144] Embodiment 25

[0145] This embodiment provides a battery, which is basically the same as Embodiment 1, except that the mass ratio of the silicon-carbon composite material, graphite, conductive carbon black, polyacrylic acid, sodium carboxymethyl cellulose and styrene-butadiene rubber is 27.7:69.2:0.5:1.3:0.4:0.9, and the mass content of silicon in the silicon-carbon composite material is 70%.

[0146] Embodiment 26

[0147] The battery structure of this embodiment is basically the same as that of embodiment 1, except that:

[0148] A=30%. The porosity of the negative electrode sheet is 39%. The OI value of the negative electrode sheet is 28.

[0149] In this embodiment, the mass content of silicon in the silicon-carbon composite material is 50%.

[0150] The Dv50 of the silicon-carbon composite material in this embodiment is 11.46 μm. The average sphericity of the silicon-carbon composite material is 0.73.

[0151] The ratio of Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.229.

[0152] Embodiment 27

[0153] The battery structure of this embodiment is basically the same as that of embodiment 1, except that:

[0154] A=1.5%. The porosity of the negative electrode sheet is 24.2%. The OI value of the negative electrode sheet is 15.9.

[0155] In this embodiment, the silicon-carbon composite material includes a porous carbon substrate, silicon dispersed in the porous carbon pores, and a carbon coating layer located on the surface of the porous carbon substrate; the carbon coating layer is amorphous carbon, and the mass content of silicon in the silicon-carbon composite material is 40%.

[0156] The Dv50 of the silicon-carbon composite material in this embodiment is 9.2 μm. The average sphericity of the silicon-carbon composite material is 0.86.

[0157] The ratio of Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.184.

[0158] Comparative Example 1

[0159] This comparative example is basically the same as Example 1, except that in this comparative example, the depth of the pressure relief groove is 90 μm, the Dv50 of the silicon-carbon composite material is 3 μm, the ratio of Dv50 to the depth of the pressure relief groove is 0.033, and the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.9.

[0160] Comparative Example 2

[0161] This comparative example is basically the same as Example 1, except that in this comparative example, the depth of the pressure relief groove is 30 μm, the Dv50 of the silicon-carbon composite material is 24 μm, the ratio of the Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.8, the ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.3, the mass ratio of the silicon-carbon composite material, graphite, conductive carbon black, polyacrylic acid, sodium carboxymethyl cellulose and styrene-butadiene rubber is 73.68:23.2:0.5:1.3:0.4:0.9, the mass content of silicon in the silicon-carbon composite material is 95%, the mass percentage content A of silicon in the negative electrode active material layer is 70%, the percentage B of the projection area of ​​the bonding member 2 in the thickness direction of the battery cell to the projection area of ​​the pole piece bonded to the bonding member 2 in the thickness direction of the battery cell is 30%, and A:B=2.33.

[0162] Test Case

[0163] 1. Sphericity test method: After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the electrode, and then the negative electrode active material layer is washed off from the electrode with deionized water, and the filtrate is removed by centrifugation after ultrasonic treatment and then dried. The obtained powder is observed in the backscattering mode of a scanning electron microscope. In this mode, the contrast of the silicon-carbon composite material is brighter, which can be distinguished from graphite and conductive carbon. The image of each particle with brighter contrast in the SEM photo at a certain magnification (such as 2500 times) is analyzed by image processing software (such as Image Pro Plus) to obtain the perimeter and area of ​​each particle, and the perimeter equivalent radius r1 and area equivalent radius r2 of each particle are calculated respectively. Then the sphericity S of each particle is r2 / r1, and then the sphericity of each particle is weighted averaged by quantity, that is, the average sphericity of the silicon-carbon composite material in the negative electrode sheet is obtained.

[0164] 2. Volume distribution particle size test method of silicon-carbon composite material: The particle size Dv50 can be measured by laser particle size test method. For example, the Malvern particle size tester is used for measurement. The test steps are as follows: the silicon-carbon composite material is dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02-0.03wt%) to form a mixture, the mixture is ultrasonicated for 2 minutes, and then placed in the Malvern particle size tester for testing.

[0165] 3. Porosity test method: gas replacement method is used for testing. The specific method is as follows: after discharging the lithium-ion secondary battery to 0% SOC, disassemble and take out the negative electrode plate, soak it in dimethyl carbonate (DMC) solvent for 12 hours and then rinse it with DMC to remove the lithium salt attached to the plate. After drying, use a slicer to cut the negative electrode plate into discs with a diameter of 12 mm, measure the thickness of 20 discs with a micrometer, calculate the volume of each disc separately and sum them to obtain the sum of the volumes of the 20 discs V1; then use a true density meter (such as JW-M100A fully automatic true density tester) to test the true volume V2 of the 20 discs, where the test gas is helium and the test environment temperature is 25±2°C; the porosity of the negative electrode plate is (V1-V2) / V1*100%.

[0166] 4. OI value test method: After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode is disassembled and taken out, and then immersed in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the electrode. After drying, it is tested with an X-ray powder diffraction instrument (such as Shimadzu XRD-6100 X-ray diffractometer). The diffraction peak appearing at 2θ=54-55° in the obtained diffraction spectrum is the (004) peak of graphite, and the intensity is recorded as I004. The diffraction peak appearing at 2θ=77-78° is the (110) peak of graphite, and the intensity is recorded as I110. The OI value of the negative electrode is I004 / I110.

[0167] 5. Cycle capacity retention rate test

[0168] At 25°C, the battery was charged to 4.45V at 1C constant current, then charged to a cut-off current of 0.05C at constant voltage, left to stand for 5 minutes, and discharged to 3.0V at 1C constant current. This was the first cycle, and the above process was repeated 300 times. The capacity retention rate was calculated according to the capacity retention rate (%) of the battery after 300 cycles = discharge capacity after 300 cycles / discharge capacity after the first cycle × 100%.

[0169] 6. Thickness expansion rate test

[0170] The initial PPG thickness of the battery at 50% SOC before the test cycle is recorded as P1. After 300 cycles, the PPG thickness of the test battery at 100% SOC is recorded as P2. The thickness expansion rate % = (P2-P1) / P1×100%.

[0171] 7. Safety performance test: Charge the battery to 4.45V at 3C at 25℃, with a cut-off current of 0.2C, and then discharge it to 3V at 0.5C. Repeat the charge and discharge steps 20 times, disassemble the battery and observe the lithium deposition of the battery.

[0172] 8. Drop test: At 25℃±5℃, discharge the battery to the lower voltage limit at 0.2C; let it stand for 10 minutes; charge it to the upper voltage limit at 1C, with a cutoff current of 0.02C, and let it stand for 10 minutes; drop the fully charged battery freely from a height of 1 meter onto a concrete board or metal floor at 25℃. If there is no fire or explosion, the test is passed. A total of 3 tests are conducted.

[0173] 9. Oven temperature test: Place the fully charged battery in an oven and heat it at a rate of 5±2℃ / min. When the temperature in the oven reaches 130℃, keep the temperature constant for 60 minutes. If there is no fire or explosion, the test is passed. The test is repeated 3 times in total.

[0174] 10. Depth of pressure relief groove: Use a scanning electron microscope to test the thickness of the cross-section groove.

[0175] 11. Thickness of the cover plate: Conventional thickness measurement method: if the cover plate is disassembled, the thickness can be directly measured with a micrometer. If the cover plate is not disassembled, the thickness can be measured with CT scanning.

[0176] 12. The mass percentage of silicon in the negative electrode active material layer: The test is conducted by thermogravimetric analysis. The specific method is as follows: After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode plate is disassembled and taken out, and then soaked in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the plate. After drying, the plate is treated at 400℃ in an inert atmosphere for 2 hours (such as a tube furnace, nitrogen or argon atmosphere). The negative electrode active material layer can be peeled off from the current collector and the negative electrode active material is collected. In the silicon content test, a thermogravimetric analyzer (such as TGA550 thermogravimetric analyzer) is used, the sample amount for the test is 5-15 mg, and the temperature is increased from room temperature to 900℃ at a rate of 10℃ / min in an air or oxygen atmosphere, and the temperature is kept at 900℃ for 40 minutes, so that the non-silicon components in the negative electrode material active layer are volatilized and the silicon can be fully oxidized to silicon dioxide. The weight percentage at the end of the entire test process is the ash content of the negative electrode active material layer; the ash value is divided by the molar mass of silicon dioxide (60) and then multiplied by the molar mass of silicon (28) to obtain the percentage of silicon element in the negative electrode active material layer.

[0177] 13. The mass content of silicon in silicon-carbon composite materials: Thermogravimetric analysis is used for testing, for example, Shimadzu DTG-60 thermogravimetric analyzer is used for testing, and the test conditions are: sample weight 5 mg, air as atmosphere, heating rate 10℃ / min from room temperature to 900℃ and constant temperature for 40min. The relationship between the silicon content x of the composite material and the final weight residual percentage y of the entire test is x=7y / 15.

[0178] The test results are shown in Table 1.

[0179] Table 1

[0180]

[0181]

[0182] The drop test is performed in a fully charged state. From the thickness expansion rate of the fully charged battery in Table 1, it can be seen that the battery has expanded to a certain extent in a fully charged state. The drop test can reflect whether the pressure relief groove of the battery will rupture in advance after the expansion of the negative electrode sheet. If the furnace temperature test passes, it means that the pressure relief groove of the battery is broken in time during the furnace temperature test, and the heat and gas are dissipated to prevent the battery from catching fire and exploding.

[0183] From the comparison of Examples 1 to 27 and Comparative Examples 1 and 2, it can be seen that the battery of the present invention has both a high drop test pass rate and a furnace temperature test pass rate. The battery of the present invention can prevent the steel shell battery from rupturing the pressure relief groove prematurely due to excessive expansion of the negative electrode sheet during the charging and discharging process while the pressure relief groove normally realizes its pressure relief function. The pressure relief groove of Comparative Example 1 is too deep, and the expansion of the battery during full charge and cycling breaks through the pressure relief groove, resulting in deterioration of the cycle, and the drop test pass rate is 0. The Dv50 of the silicon-carbon composite material in Comparative Example 2 is 24μm, and the silicon-carbon composite material particles are too large and polarized, which may cause lithium deposition on the negative electrode and deterioration of the cycle performance, thereby causing hard expansion, and the pressure relief groove ruptures during the drop test; and the pressure relief groove is too shallow, and it cannot be broken through in time during the furnace temperature test, and the heat and gas cannot be dissipated, resulting in battery fire and explosion, and the furnace temperature test pass rate is 0.

[0184] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A battery, characterized in that: It comprises a shell and a battery core, wherein the shell is provided with a pressure relief groove, and the battery core is arranged in the shell; The battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector, and the negative electrode active material layer comprises a silicon-carbon composite material; The ratio of the particle size Dv50 of the silicon-carbon composite material to the depth of the pressure relief groove is 0.06 to 0.

6.

2. The battery according to claim 1, characterized in that At least one of the following conditions is met: (1) The particle size Dv50 of the silicon-carbon composite material is 5 to 20 μm, preferably 6 to 12 μm; (2) The depth of the pressure relief groove is 35-85 μm, preferably 40-80 μm.

3. The battery according to claim 1, characterized in that The shell comprises a body and a cover plate, the body having a receiving cavity for receiving the battery cell, the receiving cavity having an opening, and the cover plate being buckled on the opening; a bonding member is provided on a side surface of the battery cell facing the cover plate; A: B = 0.015 ~ 2; A is the mass percentage of silicon in the negative electrode active material layer; B is the percentage of the projected area of ​​the adhesive in the thickness direction of the battery cell to the projected area of ​​the electrode bonded by the adhesive in the thickness direction of the battery cell; Optionally, A is 1.5% to 40%; Optionally, B is 20% to 95%.

4. The battery according to claim 3, characterized in that The pressure relief groove is arranged on the cover plate; Optionally, the pressure relief groove satisfies at least one of the following conditions: (1) The projection of the pressure relief groove and the bonding member in the thickness direction of the shell is staggered; (2) The pressure relief groove and the projection of the negative electrode sheet in the thickness direction of the shell are staggered.

5. The battery according to claim 4, characterized in that The ratio of the depth of the pressure relief groove to the thickness of the cover plate is 0.35 to 0.9, preferably 0.45 to 0.8; Optionally, the depth of the pressure relief groove is 35 to 85 μm, preferably 40 to 80 μm; Optionally, the cover plate has a thickness of 70 to 200 μm, preferably 70 to 160 μm.

6. The battery according to any one of claims 1 to 3, characterized in that: The average sphericity of the silicon-carbon composite material is 0.5-1.

7. The battery according to any one of claims 1 to 3, characterized in that: The porosity of the negative electrode sheet is 5% to 50%.

8. The battery according to any one of claims 1 to 3, characterized in that: The OI value of the negative electrode sheet is 3-35.

9. The battery according to any one of claims 1 to 3, characterized in that: The silicon-carbon composite material comprises a porous carbon substrate, silicon dispersed in the porous carbon pores, and a carbon coating layer located on the surface of the porous carbon substrate; Optionally, the carbon coating layer is amorphous carbon; Optionally, the mass content of silicon in the silicon-carbon composite material is 30% to 90%, preferably 35% to 70%.

10. The battery according to claim 9, characterized in that The silicon-carbon composite material comprises open pores and / or closed pores, wherein the closed pores refer to the pores in the porous carbon substrate that are covered by the carbon coating layer, and the open pores refer to the pores on the porous carbon substrate that are not covered by the carbon coating layer; Optionally, the area of ​​the open pores is smaller than the area of ​​the closed pores.

Citation Information

Patent Citations

  • Battery

    CN114204108A

  • Battery cell, battery and electric equipment

    CN116759627A

  • Silicon-carbon negative electrode material, preparation method and application

    CN118156472A

  • Silicon-carbon composite negative electrode material, preparation method and application

    CN118173769A

  • Battery and battery module

    CN219979751U

Cited By

  • Negative plate, preparation method of negative plate and battery

    CN121862688A